The formation of future military medical’s skills in the organization of medical support for the troops - V. N. Tregubov; S. G. Zakharov; V. A. Shcherbak; D. V. Gavryuchenkov (Сеченовский вестник)
The aim of this research is to improve the quality of practical skills that are formed in future military doctors specialized in the organization of medical support. The work was performed in the department of the organization of medical support of military training center at the I.M. Sechenov First Moscow State Medical University.